Tourism Object Development Strategy and Increasing Regional Original Income in the City of Bandung - Ajie Giyatmiko Sugiyat (Institute of Computer Science (IOCS), 2022)
The development of tourism in Indonesia is currently being pushed to become one of the sectors that contributes greatly to economic development and improving people's welfare. This is driven by the development of Indonesian tourism which continues to increase from time to time, as can be seen from the increasing number of tourists visiting tourist destinations in Indonesia, which are famous for their natural beauty, friendly people, and cultural diversity. At the regional level, this sector is expected to be a supporter of regional income whose contribution in the future has favorable prospects. This study uses a qualitative method with the aim that there is greater spontaneity and better adaptation of the interaction between researchers and research sources in obtaining answers to research questions. There are various data collection methods in this qualitative research, namely observation, textual analysis and interviews (individual or group). So the results of this study explain that, the development of tourism objects is one of the efforts made by local governments in their efforts to develop tourist objects so that later it will attract many tourists, both domestic and foreign tourists to always enjoy a series of tourism programs that have been managed and packaged. by local parties, besides that the number of tourist visits also seems to have an effect on Regional Original Income (PAD), which is the main measure of the success of the implementation of regional autonomy, and it is hoped that with regional autonomy, the independence of a region can be realized through the structure of Regional Original Income (PAD). the strong one. With the success of the Bandung city government in getting the determination of the city of Bandung as one of the world's tourist destinations as set by the UNESCO world body on September 25, 2013 in the city of Beijing is proof of the seriousness of the Bandung city government in carrying out development in the field of tourism. In addition, tourism can also have an impact on economic growth because one of them can create very wide employment opportunities, affect state income, and is able to generate foreign exchange from tourist spending. is expected to move the regional economy in a positive direction by creating new jobs and increasing income for certain regions.